Le Niveau De Capitalisation Et La Solidite Bancaire : Une Relation Controversee (Global Journal of Management and Business Research, 2018)
In this article we review the literature on the relationship between the capitalization requirement and the ability of the bank to withstand a shock. The theoretical literature review reveals a controversy about the relationship between the level of capitalization and bank robustness. On the basis of portfolio selection theory, a binding capitalization requirement can lead to an increase in risk taking. Conversely, the state preference theory argues for the positive effect of the capitalization requirement on bank robustness.
Keywords: capitalization requirement; portfolio choice; capacity